Ultrafast Recovery of Hydrophobic Particles Using a Novel Hydrophobic Binder Medium - T. P. Ernst; K. van Netten (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
"Froth flotation has been used successfully for about a century in the beneficiation of both coal and mineral particles. With the on-going trend towards lower feed grades, however, there is a need to transform this technology in ways that can deliver ultrafast separations, with strong selectivity, and recovery, covering a broader size range. It should be recognised that the hydrophobic effect, with its highly selective and long-range interactions, will most likely underpin any new technology. We identified the separation of the concentrate from the tailings as the rate determining step of conventional flotation technology. This limitation was then addressed by developing a novel flotation technology, insuring the formation of a concentrate that could be separated more rapidly from the tailings. We introduced a novel binder medium, a highly concentrated water in oil emulsion, to act as the focal point for hydrophobic adhesion, effectively replacing the air bubbles used in conventional flotation. The hydrophobic particles adhere to and become embedded within the binder, forming saturated agglomerates that float upwards. Moreover, by forming these large and resilient agglomerates, the product can be quickly dewatered over a screen and separated almost immediately from the tailings. Remarkably, this new binder permits residence times in the order of a few seconds under batch conditions. This paper examines the performance of the technology as a function of the oil wt% added to the slurry. The paper also examines the performance of the technology as a function of the particle size, showing a decline as the particle size exceeds 0.50 mm.INTRODUCTIONFroth flotation involves the collision and adhesion of hydrophobic particles to rising air bubbles, the carrying of those particles from the bubbly-pulp zone into a froth zone, and subsequent drainage and migration of the pulp to achieve the final concentrate (Wills, 2006). Within a Jameson Cell the feed slurry and air bubbles are brought into intense contact within the active area of the downcomer, achieving rapid kinetics of hydrophobic particle adhesion to the air bubbles (Harbort et al., 1994). However, once the bubble laden product and tailings emerge from the downcomer there is the need for separation of the concentrate from the tailings, an inherently slower process. In other devices such as mechanical cells the initial kinetics of particle adhesion are far slower, relying on the turbulent eddies throughout the cell, while in a column the kinetics rely upon an even slower process of bubble interception with suspended and settling particles (Gorain, 2007). However, in all cases the driving force for segregating the bubbles from the tailings, and the drainage of the froth are inherently the same. We do note, however, recent advances by Galvin and co-workers in achieving so-called Fast Flotation, utilizing a system of inclined channels to dramatically increase the segregation rate of bubbles from the tailings, permitting much higher gas and feed fluxes to be applied, achieving up to a ten-fold throughput advantage (Dickinson et al., 2014). Any further improvement within the existing flotation paradigm would require the introduction of centrifugal forces, but this would also require the formation of much finer bubbles than is typically used given the tendency of relatively large bubbles to reach a limiting slip velocity due to deformations and increased drag. Across all flotation devices we argue the rate determining step remains the segregation of the bubbles from the tailings."